Increasing productivity and profitability: Evaluating diverse and intensifying cropping systems. A field study in Rajshahi District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Hossain, Shakhawat; Md. Arifur Rahaman; Hossain, M. Khaled; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
The Barind Tract in the Rajshahi region of Bangladesh spans 160,000 hectares and experiences high temperatures, limited soil moisture storage, and low, erratic rainfall. The land is characterized by poor drainage, low organic matter content, and a high susceptibility to drought, leading to low crop productivity (Rashid et al., 2019). A farmers' participatory research trial was conducted on diversified, intensified, and climate-resilient cropping system options, comparing farmers’ traditional cropping systems with those developed in collaboration with the Bangladesh Agricultural Research Institute and the Bangladesh Wheat and Maize Research Institute. A research brief has been prepared to summarize the results of the study, focusing on productivity and economic efficiency from 2022-23 in the Rajshahi district, Bangladesh.